s11f1036

s11f1036 - Solution for assignment 36 With H= qj ˙ j ∂L...

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: Solution for assignment 36: With H= qj ˙ j ∂L − L ∂ qj ˙ we find dH = d j ∂L ∂ qj ˙ qj + ˙ ∂L ∂L ∂L dqj − ˙ dqj − ˙ dqj ∂ qj ˙ ∂ qj ˙ ∂qj . The two central terms cancel out. Using Euler-Lagrange and the definition of the generalized momentum, we have d ∂L ∂L = = pj ˙ ∂qj dt ∂ qj ˙ and, therefore, (qj dpj − pj dqj ) . ˙ ˙ dH = j From this we read off Hamilton’s equations: ∂H = qj ˙ ∂pj and ∂H = −pj . ˙ ∂qj ...
View Full Document

This note was uploaded on 12/11/2011 for the course PHY 4936 taught by Professor Berg during the Fall '11 term at FSU.

Ask a homework question - tutors are online